Stories transmitted through art for the revitalization and decolonization of the Arctic - Jokela, Timo; Huhmarniemi, Maria (Routledge, 2021)
This chapter is a narrative description and theoretical conceptualization of the premises, processes, execution and results of a place-specific public art project by Professor Jokela. The Story of Kirkkokuusikko is a memorial to the first Christian church in the Kittilä region in Finnish Lapland. The story of the church conveyed the memories and worldview of the Kemi-Lapland Forest Sámi, their social system and the arrival of Finnish settlers and Christianity in the region. The memorial was connected to the stories of the past, but the dialogue and process involved in making the artwork were very important for the locals, whose background and cultural roots lie partly in the forgotten and overlooked Kemi-Lapland Forest Sámi culture. The case study of the memorial shows how place-based art can function as place-conscious art education, regional identity development, a revitalization effort and a decolonization strategy. Interwoven art-based research and place-specific strategies have the potential to foster revitalization and decolonization in rapidly changing multi-ethnic communities in the North and the Arctic. Revitalization and decolonization are not only about people but also about places, regions and nature. This chapter is a narrative description and theoretical conceptualization of the premises, processes, execution and results of a place-specific public art project by Professor Jokela. The Story of Kirkkokuusikko is a memorial to the first Christian church in the Kittilä region in Finnish Lapland. The story of the church conveyed the memories and worldview of the Kemi-Lapland Forest Sámi, their social system and the arrival of Finnish settlers and Christianity in the region. The memorial was connected to the stories of the past, but the dialogue and process involved in making the artwork were very important for the locals, whose background and cultural roots lie partly in the forgotten and overlooked Kemi-Lapland Forest Sámi culture. The case study of the memorial shows how place-based art can function ...